Comparative analysis between patients undergoing Gastric Bypass and Sleeve Gastroplasty in a private hospital in Sao Luis-MA - Lima,Rodrigo Lira Sousa (2020)
Abstract Purpose: To compare the satisfaction levels about the surgery and anesthesia management, and to analyze the postoperative outcomes of patients undergoing Gastric Bypass and Sleeve Gastroplasty surgeries in a private hospital in Sao Luís-MA. Methods: The sample consisted of patients undergoing Bypass and Sleeve bariatric surgeries from August 2018 to August 2019, who were in the range of 18 and 70 years old and had not used drugs or presented cardiac arrhythmias, dilated cardiomyopathy, and conduction disorder heart. Data were collected from the evaluation forms and recorded in a form with closed questions. Results: Most patients were female (Bypass – 56% and Sleeve – 67.4%) and aged between 30 and 39 years old (Bypass – 32% and Sleeve – 55.8%). Information (Bypass – 92% and Sleeve – 86.1%) was the highest satisfaction index found. Sleepiness in the immediate postoperative period (Bypass – 92% and Sleeve – 93%) was the main side effect. There were no postoperative complications in patients between the two types of surgery. Conclusions: Patients submitted to Bypass and Sleeve were completely satisfied with the perioperative management. There was no statistically significant difference when comparing adverse effects between the techniques.